Оцінювання напруженого стану в елементах компоновки низу бурильної колони за випадкових динамічних навантажень - Гриджук, Я.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
By means of mathematical model of longitudinal fluctuations of a boring column kinematic transfer functions of boring columns of five configurations are calculated, the interrelation between speed of the top and bottom part of a boring column is established. Behind the received size of the maximum speed the size of the maximum pressure is defined.